Recovering the U.S. Hispanic literary heritage. - Gonzales-Berry, Erlinda, 1942-; Tatum, Charles M. (Arte Público Press, 1996)
This second volume in the series contains articles by the leading scholars on Hispanic literary history of the United States given at the annual convention on Recovering the U.S. Hispanic Literary Heritage. The articles in this volume are in five sections.